Avaliação de mecanismos de resistência ao pulgão Rhopalosiphum padi (Hemiptera: aphididae) em cultivares de trigo - Peruzzo, Rafael (2007)
Aphids (Hemiptera: Aphididae) are important pests of the winter cereals, mainly, in wheat (Triticum aestivum) so much for the damage that cause by sucking the sap, as for the viroses transmission to the plants. The occurrence of Rhopalosiphum padi (Linnaeus, 1758) has been increasing significantly in wheat in the south of Brazil. The biological control, that occurs naturally, and the use of chemical insecticides are not efficient to avoid the damages caused by aphids. The resistance of plants to insects is considered the ideal method of control because the possibility to integrate with other control methods that not cause damage to the enviroment and without additional costs to the farmer. Four experiments were led in laboratory controlled conditions and one experiment in greenhouse conditions, whith the objective to evaluate the resistance mechanisms to the bird cherry oat (R. padi) in eight wheat commercial cultivars (BRS 194, BRS 208, BRS Camboatá, BRS Guabiju, BRS Guamirim, BRS Louro, BRS Timbaúva e BRS Umbu). The results showed that BRS Guamirim and BRS Louro cultivars were the most prefered and BRS Timbaúva cultivar the least prefered by winged aphids. The BRS Timbaúva cultivar when used as host of R. padi, caused decrease in the insects longevity, fecundity and survival. The BRS Timbaúva cultivar was the most resistant to the aphid R. padi considering development and production capacity of plants